Correlation of pressuremeter test, Dutch cone test, and standard penetration test in first stiff clay and first sand layers in Rangsit clay - Ruj Neeyapan; Bergado, Dennes T.; Chandra, Sarvesh; Rantucci, Giovanni; Starr Foundation (U.S.A.) (Bangkok : Asian Institute of Technology, 1985)
A comprehensive program of in-situ tests were carried out in the stiff clay and first sand layer at AIT campus. The three types of in-situ tests were the pressuremeter test, the Dutch Cone test and the Standard Penetration test. The Pressuremeter test can yield the parameter namely: horizontal earth pressure at rest Po, yield pressure, Py, limit pressure Pl, and deformation modulus, Ep. The Dutch cone test can yield cone resistance, Qc and local friction, Qlf. The Standard Penetration test can yield the number of blow count, N. The tests were carried out in four sites, namely behind ET building, near tennis court, hear Korea House, and football field. In each site, the Dutch cone test was done in five locations, at 0.2 m interval from 10.0 to 16.0 m depth. The Pressuremeter test and the Standard Penetration test were carried out in three locations at 1.0 m interval from 10.0 m to 23.0 m depth. The following correlation of in-situ soil properties were obtained. In Stiff clay: Ep = 3.1Qc + 25 (Ep/Qc = 4.52) Qc = 6.3Py + 8.7 (Qc/Py = 14) Qc = 2.55Pl* + 4.6 (Qc/Pl* = 3.24) Qc = 1.2N + 13 (Qc/N = 3.86) Ep = 8.3N N = 2.5Py + 5 (N/Py = 6.86) N = 0.4Pl* + 6.95 (N/Pl* = 1.37) In sand layer: Ep = 37 N 4̕5 N = 0.44 Pl* + 12.8 (N/Pl* = 1.03) N = 1.9 Py + 13.9 (N/Py = 5.44) Furthermore, laboratory test results (from the direct shear test) was correlated with pressuremeter test in sand layer (o - value) as following: od = 0.12op + 29.2 (od/op + 0.92) The correlation obtained in this thesis has been discussed and compared with the results of past investigators. It is concluded that the soil parameters and correlation factors obtained in this study can be used in the evaluation of design parameters for Rangsit clay.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Clay -- Thailand -- Rangsit -- Testing